1357 Ankle Blocks: Improving Day Case Efficiency. (12th October 2021) - Doherty, C; McKenna, R; Kang, H W; Gibson, D; Hanratty, B; Wong-Chung, J
Abstract: Introduction: The COVID pandemic has exerted unprecedented pressure on hospital resources. Resulting in cancellation of elective operative services, increased patient waiting lists, limited surgical training opportunities along with reduced availability of staff, theatre, and in-patient bed capacity. A novel approach for day case forefoot surgery under ankle block, to mitigate the pandemic service limitations without compromising care, was developed. Method: This is a 3-month, multi-centre, prospective cohort study evaluating the novel ankle block day case forefoot surgery pathway. Patients had a minimum of three months clinical follow up with outcome scores. They were matched to a cohort undergoing similar surgery prior to the COVID pandemic. Results: The utilisation of an ankle block pathway resulted in an average reduction of inpatient stay by 2 days per patient. Over the study period conservative savings of £26, 659 were calculated. Anecdotally we observed a reduction in morbidity (wound complications, SSI's) although not statistically significant. Conclusions: Our novel surgical pathway has enabled continued elective operating for procedures that previously required hospital admission during a period of severe restrictions within the NHS. We observed significant reductions in cost, surgical inpatient bed utilisation and total operative time with staff, resource, and time savings. We hypothesise that prehabilitation with physiotherapy, ankle instead of thigh tourniquets and early mobilisation may have contributed to improved morbidity scores. The findings of this project have implications for training, upper limb services and are transferrable as a template to improve service efficiency while maintaining high quality care.